2017
DOI: 10.1093/glycob/cwx007
|View full text |Cite
|
Sign up to set email alerts
|

Binding Characteristics of Galectin-3 Fusion Proteins

Abstract: Galectin-3 modulates cell adhesion and signaling events by specific binding and cross-linking galactoside containing carbohydrate ligands. Proteolytic cleavage by metalloproteinases yields in vivo N-terminally truncated galectin-3 still bearing the carbohydrate recognition domain. Truncated galectin-3 has been demonstrated to act in vivo as a negative inhibitor of galectin-3 due to higher affinity for carbohydrate ligands. We here present our studies on a series of 12 human galectin-3 protein constructs. Trunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 69 publications
13
23
1
Order By: Relevance
“…Gal‐3 binding to the immobilized glycopolymer yielded typical sensorgrams (Figure A). This is in contrast to SPR measurements using an immobilized standard glycoprotein, asialofetuin, that gave plateau‐like curves without distinct association and dissociation phases …”
Section: Resultscontrasting
confidence: 76%
See 3 more Smart Citations
“…Gal‐3 binding to the immobilized glycopolymer yielded typical sensorgrams (Figure A). This is in contrast to SPR measurements using an immobilized standard glycoprotein, asialofetuin, that gave plateau‐like curves without distinct association and dissociation phases …”
Section: Resultscontrasting
confidence: 76%
“…Protein concentrations were measured by the Bradford assay using bovine serum albumin (BSA, Carl Roth, Karlsruhe, Germany) for calibration. For testing the full binding properties, an ELISA‐type binding assay was performed using immobilized asialofetuin …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose APEX2 over other peroxidase enzymes, due to its monomeric nature, small size (28 kDa), and improved activities in various cellular compartments [16], especially for proteomic applications [20]. We fused APEX2 to the N-terminus of galectin-3, as previous work has shown that such fusion proteins remain active towards binding glycans [21]. Both fusion proteins were generated efficiently (Figs.…”
Section: Proximity Tagging To Identify Galectin-3 Interactors In Hepamentioning
confidence: 99%